Writing and communication in early Egyptian monasticism - Choat, Malcolm.; Giorda, Mariachiara. (Texts and Studies in Eastern Christianity, 2017)
As senders of letters, copyists of literary texts, compilers of accounts, readers, and teachers, the monks of late antique Egypt articulated their interactions with their ascetic and secular environments via their role as authors, scribes, and owners of written text. This volume edited by Malcolm Choat and Maria Chiara Giorda examines the presence and practice of writing, modes of written communication, and the symbolic and spiritual value of the written word in monastic communities. Contributions cover evidence from papyri and inscriptions to literature transmitted in manuscripts, positioned within the shift in recent scholarship away from literature such as hagiography as a source of positivistic history, towards evidence that derives more directly from the monk or period in focus.